2005
DOI: 10.1021/ja0511669
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Lithography of Phospholipid Bilayer Films by Stereoselective Hydrolysis

Abstract: The stereoselective phospholipase A2-catalyzed hydrolysis of patterned phospholipid bilayers consisting of the l- and d-isomers of alpha-dilauroylphosphatidylcholine (DLPC) and alpha-dipalmitoylphosphatidylcholine (DPPC) is reported. The stereochemically directed enzyme lithography demonstrated herein allows the parallel modification of large surface areas and constitutes a potentially useful method to structure biomimetic films, given the stereospecific action of many enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As reported previously, the lipid bilayer can be hydrolyzed by the bee venom PLA 2 under similar conditions 11a. d The supported bilayer was set to a flow‐cell with a Tris‐buffer solution (pH 8.9, 10 m M Tris, 100 m M NaCl) with 5 m M CaCl 2 and then analyzed by SFG.…”
Section: Methodsmentioning
confidence: 81%
“…As reported previously, the lipid bilayer can be hydrolyzed by the bee venom PLA 2 under similar conditions 11a. d The supported bilayer was set to a flow‐cell with a Tris‐buffer solution (pH 8.9, 10 m M Tris, 100 m M NaCl) with 5 m M CaCl 2 and then analyzed by SFG.…”
Section: Methodsmentioning
confidence: 81%
“…It catalyzes the hydrolysis of L-isomers stereoselectively, of the phospholipid bilayers made up of the l-and d-isomers of ␣-dipalmitoylphosphatidylcholine (DPPC) and ␣-dilauroylphosphatidylcholine (DLPC). The report demonstrates that the stereospecific action of enzyme can be exploited to modify polymer surface stereochemically [79]. Chow et al, has reported the use of deoxynucleotidyl transferase enzyme for enzymatic fabrication of DNA nanostructures.…”
Section: Enzyme Lithographymentioning
confidence: 92%
“…The enzyme, one kind of biological catalyst, can promote chemical and biochemical reactions with high efficiency and specificity. Catalyzing surface chemical and biochemical reactions using enzymes at the nanoscale in a controlled fashion is extremely attractive in the field of manufacturing and manipulating 1–11. Until now, many methods, such as microcontact printing (μCP)12–14 and scanning probe microscopy (SPM)‐based lithography,1, 3–5, 7–11, 15 have been used to pattern micro‐ and nanometer enzyme features.…”
Section: Methodsmentioning
confidence: 99%